2019
DOI: 10.1155/2019/6496901
|View full text |Cite
|
Sign up to set email alerts
|

Possible Improvement of the Sagittal Spinopelvic Alignment and Balance through “Locomotion Training” Exercises in Patients with “Locomotive Syndrome”: A Literature Review

Abstract: On the basis of rapid population aging, in 2007, the Japanese Orthopaedic Association (JOA) proposed a new disease concept “locomotive syndrome” as a degenerative condition of reduced mobility due to the impairment of the musculoskeletal system. Worsened locomotive components, which consist of bones, joints, and intervertebral discs, and muscles and nerves, can lead to symptoms such as pain, limited range of motion, malalignment, impaired balance, and difficulty in walking, ultimately resulting in the requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Kazzman et al 21) reported that a spine-strengthening exercise with postural training for older adults reduced spinal hyperkyphosis and improved the patients' self-image, including increased satisfaction with their appearance. The term "locomotive syndrome" was proposed by the Japanese Orthopedic Association in 2007 as a condition of reduced mobility due to the impairment of locomotive organs; many reports have revealed the effectiveness of physical intervention for elderly people in preventing the locomotive syndrome and the decline in activities of daily living 22,23) .…”
Section: Discussionmentioning
confidence: 99%
“…Kazzman et al 21) reported that a spine-strengthening exercise with postural training for older adults reduced spinal hyperkyphosis and improved the patients' self-image, including increased satisfaction with their appearance. The term "locomotive syndrome" was proposed by the Japanese Orthopedic Association in 2007 as a condition of reduced mobility due to the impairment of locomotive organs; many reports have revealed the effectiveness of physical intervention for elderly people in preventing the locomotive syndrome and the decline in activities of daily living 22,23) .…”
Section: Discussionmentioning
confidence: 99%
“…Yurube et al. also reported two cases of improved SVA by exercise training, suggesting that strengthening of the back and lower extremity muscles, in addition to their improved flexibility, can improve sagittal spinal alignment [ 27 ]. Moreover, locomotion training has been reported to reduce fall rates and improve SVA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hori et al investigated the relationship between trunk muscle strength and SVA, and suggested that lower muscle strength in the trunk was associated with a higher SVA [26]. Yurube et al also reported two cases of improved SVA by exercise training, suggesting that strengthening of the back and lower extremity muscles, in addition to their improved flexibility, can improve sagittal spinal alignment [27]. Moreover, locomotion training has been reported to reduce fall rates and improve SVA [28].…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, IDD is associated with neurological impairments including radiculopathy, myelopathy, and paralysis 3 and impaired daily activities of the elderly. 5 Biochemically, IDD is characterized by the loss of extracellular proteoglycan matrix due to increased catabolism from persistent matrix homeostatic imbalance. 6 Matrix degradation is a consequence of increased activities of catabolic enzymes, including matrix metalloproteinases (MMPs) and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTSs), and/or decreased activities of tissue inhibitors of metalloproteinases (TIMPs).…”
Section: Introductionmentioning
confidence: 99%